2012
DOI: 10.1016/j.biopsych.2011.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Glutamic Acid Decarboxylase 67 Deficiency Results in Lower Cannabinoid 1 Receptor Messenger RNA Expression: Implications for Schizophrenia

Abstract: Background Levels of cannabinoid 1 receptor (CB1R) mRNA and protein, which are expressed most heavily in the cholecystokinin class of GABA neurons, are lower in the dorsolateral prefrontal cortex (DLPFC) in schizophrenia, and the magnitude of these differences is strongly correlated with that for glutamic acid decarboxylase (GAD67) mRNA, a synthesizing enzyme for GABA. However, whether this correlation reflects a cause-effect relationship is unknown. Methods Using quantitative in situ hybridization, we measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Many previous studies 7,8,45,46 have focused on the relationship between CAD and SCZ, whereas the correlation between CAD and MDD has received much less attention. Although depressive disorders are highly comorbid with CAD in clinical settings, 47 to our knowledge no previous genomics study has explored CAD-MDD pleiotropy.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies 7,8,45,46 have focused on the relationship between CAD and SCZ, whereas the correlation between CAD and MDD has received much less attention. Although depressive disorders are highly comorbid with CAD in clinical settings, 47 to our knowledge no previous genomics study has explored CAD-MDD pleiotropy.…”
Section: Discussionmentioning
confidence: 99%
“…In tissue sections from human subjects with schizophrenia a variety of GABA-related deficits have been observed. Specifically, studies of frontal cortex tissue have shown reductions in GAT-1 (30) and GABA A R α1 mRNA expression and reduced density of ankyrin-G immunoreactivty (31) along with an increase in α2 expression (32) along axon-initial segments, as well as deficits in transcripts encoding CCK (33) and cannabinoid 1 receptor (34).…”
Section: Discussionmentioning
confidence: 99%
“…In the first stage, LCN attains their mature fates, defined by their distinctive connectivities, neurochemistries, and firing properties, which culminate in their attaining distinct functions within juvenile cortical circuits (Ascoli et al, 2008). A detailed discussion of this process is beyond the scope of this review, but interacting influences of transcription factors (Close et al, 2012;Cobos et al, 2005), neurotransmitters (Eggan et al, 2012), neurotrophins (Huang et al, 1999), cell adhesion molecules (Pillai-Nair et al, 2005), and their activities are clearly in play (Bartolini et al, 2013;Batista-Brito and Fishell, 2009). The second stage of LCN maturation occurs in concert with cortical circuitry maturation, a process that begins in the early postnatal time period but is not finally achieved in all cortical regions until adolescence or young adulthood.…”
Section: Postmigratory Maturationmentioning
confidence: 99%